Revisiting bacterial cytolethal distending toxin structure and function - Chen, Henry; Ang, Claire J.; Crowder, Molly K.; Brieher, William M.; Blanke, Steven R. (Frontiers in Cellular and Infection Microbiology, 2023)
Cytolethal distending toxins (CDTs) are intracellular-acting bacterial genotoxins generated by a diverse group of mucocutaneous human pathogens. CDTs must successfully bind to the plasma membrane of host cells in order to exert their modulatory effects. Maximal toxin activity requires all three toxin subunits, CdtA, CdtB, and CdtC, which, based primarily on high-resolution structural data, are believed to preassemble into a tripartite complex necessary for toxin activity. However, biologically active toxin has not been experimentally demonstrated to require assembly of the three subunits into a heterotrimer. Here, we experimentally compared concentrationdependent subunit interactions and toxin cellular activity of the Campylobacter jejuni CDT (Cj-CDT). Co-immunoprecipitation and dialysis retention experiments provided evidence for the presence of heterotrimeric toxin complexes, but only at concentrations of Cj-CdtA, Cj-CdtB, and Cj-CdtC several logs higher than required for Cj-CDTmediated arrest of the host cell cycle at the G2/M interface, which is triggered by the endonuclease activity associated with the catalytic Cj-CdtB subunit. Microscale thermophoresis confirmed that Cj-CDT subunit interactions occur with low affinity.Collectively, our data suggest that at the lowest concentrations of toxin sufficient for arrest of cell cycle progression, mixtures of Cj-CdtA, Cj-CdtB, and Cj-CdtC consist primarily of non-interacting, subunit monomers. The lack of congruence between toxin tripartite structure and cellular activity suggests that the widely accepted model that CDTs principally intoxicate host cells as preassembled heterotrimeric structures should be revisited.